2022
DOI: 10.1097/md.0000000000031168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transversus abdominis plane block on the quality of recovery in laparoscopic nephrectomy: A prospective double-blinded randomized controlled clinical trial

Abstract: Background: Poorly controlled acute postoperative pain after laparoscopic nephrectomy may adversely affect surgical outcomes and increase morbidity rates. In addition, excessive use of opioids during surgery may slow postoperative endocrine and metabolic responses and cause opioid-related side effects and opioid-induced hyperalgesia. The purpose of this study was to evaluate the effect of ultrasound-guided transversus abdominis plane (TAP) block on the postoperative quality of recovery and intraoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…However, even if in our study, we demonstrated TAPB to be inferior to ESPB; an analgesic strategy with TAPB achieves great benefits compared to standard analgesic treatments in the first 24-48 h after surgery in terms of pain scores and overall opioid consumption. In fact, TAPB has been described to be effective in analgesic pain control with a reduction in opioid consumption even in urologic surgery with good results in either radical robotic-assisted prostatectomies [20], laparoscopic nephrectomies [21], and percutaneous nephrolithotomy [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if in our study, we demonstrated TAPB to be inferior to ESPB; an analgesic strategy with TAPB achieves great benefits compared to standard analgesic treatments in the first 24-48 h after surgery in terms of pain scores and overall opioid consumption. In fact, TAPB has been described to be effective in analgesic pain control with a reduction in opioid consumption even in urologic surgery with good results in either radical robotic-assisted prostatectomies [20], laparoscopic nephrectomies [21], and percutaneous nephrolithotomy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Four injection sites were chosen for all pelvic procedures, while for nephrectomies, we opted for three injection sites: two subcostal and one lateral on the intervention side [8]. The latter enabled us to inject concentrations of ropivacaine in the organ extraction area requiring a surgical enlargement of the trocar edge [21] higher than in the two subcostal bilateral sites, aimed at attenuating pain from pneumoperitoneum overdistension. The total volume for each site was always 20 mL as in numerous previous studies and the ropivacaine total dose was determined as the maximal safe dose.…”
Section: Discussionmentioning
confidence: 99%
“…The subcostal TAP block has since been shown to provide postoperative analgesia and reduce open consumption for patients undergoing both open and laparoscopic upper abdominal surgery. 28,29,30 Strengths An undoubted strength of our study is that the regional analgesia technique will be performed by, or under the direct supervision of, the same consultant anaesthesiologist, while the surgery will be performed by the same consultant surgeon, for the duration of the study. Any difference in outcome which may have been contributable to variations in either anaesthetic or surgical approach of different consultants will as such be eliminated.…”
Section: Erector Spinae Plane Blockadementioning
confidence: 99%